PENERAPAN METODE OUTDOOR STUDY BERBANTUAN MEDIA QUIZIZZ TERHADAP MINAT BELAJAR GEOGRAFI SISWA DI SMA NEGERI 1 BUSUNGBIU - Putra, I Made Widnyana Pramana; Sriartha, I Putu; Citra, I Putu Ananda (STKIP Pesisir Selatan, 2025)
This study aims to analyze: (1) the application of the outdoor study method containing local wisdom assisted by the quizizz media in geography learning and (2) the effect of the outdoor study method containing local wisdom assisted by the Quizizz media on students' learning interest. This study employs a quasi-experimental design featuring a non-equivalent control group. The sample for the class was randomly selected among equivalent class pairs, designating class X1 as the experimental group and class X6 as the control group. Data was gathered by observation, testing, and documentation procedures, followed by analysis utilizing quantitative descriptive approaches and inferential analysis via the t-test. The research results indicated that: (1) The average value of the application of the outdoor study method assisted by the quizizz media containing local wisdom in the experimental class was 96.87 and in the control class was 90.62 and (2) Based on the data tested, it resulted in the Sig value, (2-tailed) of the results of students' learning interest getting results of 0.003 <0.05. The research findings indicate that the outdoor study technique, facilitated by Quizizz media, serves as a more dynamic resource for high school geography educators to enhance student engagement in learning.